En forskare i räddningsjacka: Om forskarrollens platsbundenhet - Eliasson, Linda (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2010)
In this article the author reflects upon her field study where she follows a group of firefighters in their work. The purpose of her research is to study the interaction between the public and the professionals, such as firefighters, police and medics, at the incident site. However, when following the firefighters three different places become central to the study: the fire station, the incident site and the fire engine. Being on these different places does not only affect what the researcher is able to observe, it also affects the role of the researcher, especially when it comes to inclusion and participation. In trying to increase her sense of belonging on the field the researcher uses different strategies, where the most significant one is to dress in a way that is similar to the firefighters. By wearing a rescue jacket at the incident site the researcher is practicing and impression management that does not only legitimize her presence at the site, the jacket also makes it possible to practice field work in a way that would not have been possible without it.